Positional error and time-activity patterns in near-highway proximity studies: an exposure misclassification analysis. - Lane, Kevin J.; Kangsen Scammell, Madeleine.; Levy, Jonathan I.; Fuller, Christina H.; Parambi, Ron.; Zamore, Wig.; Mwamburi, Mkaya.; Brugge, Doug. (2016)
Background: The growing interest in research on the health effects of near-highway air pollutants requires an assessment of potential sources of error in exposure assignment techniques that rely on residential proximity to roadways.; Keywords: Highway proximity, Time-activity, Traffic, Geocoding, Exposure misclassification.; Springer Open.